Development Learning Device Model of Environmental Education in the Character of Environmental Care at Senior High School in Solok Selatan Regency - Maisardi, Maisardi (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
Implementation of environmentally caring education in schools requires teachers to develop learning tools that can lead learners to achieve the expected growth of character. The purpose of this research to produce learning devices of environmental education (PLH) that can grow this characters in high school students in Solok Selatan Regency. Development method using the 4-D model which consists of four stages of defining, design, development and disseminate. Learning tools developed in the form of the syllabus, Lesson Plan, and students worksheet. The result of document analysis of learning devices shows that during this implementation of environmental character education through PLH at senior high school in Solok Selatan Regency has not been done properly. It is necessary to develop effective learning tools effectively to build the environmental caring character of learners. As a proven from the analysis of the validity of learning devices showed in a very good category, the device practicability by the teacher was very good and by the students of the good category. Effectiveness device seen from the learning of cognitive domain and effective were also in the good category. The character formed through the development of learning tools PLH classified into 2, namely individual characters, among others: religious, disciplined, creative, independent. Then the second was the social character, among others: environmental care, social care, responsibility. The study of learning device development only up to stage three development of four stages of development of the 4-D model. It would be better if the development model was done until the disseminate stage so that learning devices can be developed on a wider scale.